1990
DOI: 10.1111/j.1751-0813.1990.tb07694.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of high‐energy electrons to depilate the breech of sheep

Abstract: The use of high-energy electrons for permanently depilating areas of sheep skin was evaluated. The most effective dose of electrons for depilation was 17.5Gy. Histological changes in skin treated at this dose were examined in one sheep over 18 months and in 5 sheep over 89 d. Effects of treatment on bodyweight gains and fleece growth were examined by comparing the productivity of a further 5 sheep treated on the breech with high-energy electrons, with that of conventionally mulesed sheep (n = 5) and untreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This effect was short term and recovery was apparent within 3 months of irradiation. In contrast, relatively larger irradiation doses (17.5 Gy) intentionally directed within 1 to 2 mm of the ovine skin surface causes long term damage to, and loss of, wool follicles (Sorell et al, 1990). In the present experiments, radiation delivery and damage to the skin surface was calculated precisely and predicted to be minimal.…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…This effect was short term and recovery was apparent within 3 months of irradiation. In contrast, relatively larger irradiation doses (17.5 Gy) intentionally directed within 1 to 2 mm of the ovine skin surface causes long term damage to, and loss of, wool follicles (Sorell et al, 1990). In the present experiments, radiation delivery and damage to the skin surface was calculated precisely and predicted to be minimal.…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…Workers in South Australia 20,21 reported some preliminary results using a linear accelerator to produce ionising radiation that damaged mitotically active cells. Their work suggested that permanent depilation was possible.…”
Section: High Energy Electronsmentioning
confidence: 99%
“…Alternatives to mulesing have been investigated in the last 15 years or so, 48,49 but the impetus has increased significantly since the implementation of the campaign by People for the Ethical Treatment of Animals (PETA) 50 . Currently the development of a flystrike vaccine 47 and a needle‐free injection of a protein 51 are ongoing.…”
Section: The Present and Future: Reducing And Eliminating Animal Welfmentioning
confidence: 99%
“…The selection of polled genotypes of sheep would also benefit welfare, because horned rams are at risk of flystrike when fighting causes bleeding around the horns. 47 Alternatives to mulesing have been investigated in the last 15 years or so, 48,49 but the impetus has increased significantly since the implementation of the campaign by People for the Ethical Treatment of Animals (PETA). 50 Currently the development of a flystrike vaccine 47 and a needle-free injection of a protein 51 are ongoing.…”
Section: Invasive Proceduresmentioning
confidence: 99%